Answer:
-99
Explanation:
First, let's find an equation to use to make things easier.
So, as we can see, the numbers go down 3 every time and we start at 27, so, the first term is 27, that means that we need to find the number before 27, so we add 3 to 27 to get 30.
We can put the equation using y = mx + b, since that is the most appropriate formula to use.
y = -3x + 30
y = -3(1) + 30
y = -3 + 30
y = 27
y = -3x + 30
y = -3(2) + 30
y = -6 + 30
y = 24
So, this is a good equation to use. Now, we substitute 43 as x
y = -3x + 30
y = -3(43) + 30
y = -129 + 30
y = -99